A method for achieving room temperature strong circularly polarized luminescence properties in achiral organic-inorganic hybrid perovskites
By constructing a step-like energy band structure of three-layer nanosheets in achiral perovskites, using efficient spin-polarized carrier transmission on the interface, the problems of limited types of chiral perovskites and strong electroacoustic coupling are solved, and the strong circular polarization luminescence characteristics of room temperature are achieved, which broadens the application range.
Patent Information
- Application Number
- CN202310758191.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-06-26
AI Technical Summary
In the prior art, the types of chiral perovskites are limited and the electroacoustic coupling effect is strong, resulting in limited application of perovskite-based circular polarization light characteristics.
By constructing a step-like energy band structure of three-layer nanosheets in achiral perovskite, the high-efficiency spin-polarized carrier transmission of the interface is used to achieve strong circular polarization luminescence characteristics in room temperature.
In achiral perovskite, a strong circular polarization luminescence characteristic with room temperature polarization of up to 28.5%, broadening the application range of perovskite-based circular polarization luminescence.
Smart Images

Figure CN116790245B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for realizing room temperature strong circular polarization luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, belonging to the field of optoelectronic information technology. Background Art
[0002] Materials with circularly polarized light (CPL) properties have attracted much attention due to their great application potential in optoelectronics and spintronics. Recently, chiral organic-inorganic hybrid perovskite materials have shown strong CPL emission and sensitive CPL detection properties, which are of great significance in the application of chiral-spin and chiral-optoelectronic devices.
[0003] Usually, chiral perovskites are prepared by introducing chiral molecules into the perovskite structural framework. However, the types of commonly used chiral long-chain molecules are very limited. This greatly hinders the widespread application of perovskite-based CPL properties. Achiral perovskites have the advantages of rich types, high luminescence efficiency, weak electroacoustic coupling, and adjustable band gap. Therefore, if strong CPL properties can be achieved in achiral perovskites, the application range of perovskite-based CPL properties will be greatly enriched. Summary of the invention
[0004] The technical problem solved by the present invention is: in order to overcome the application limitations of perovskite-based CPL characteristics caused by the shortcomings of limited types of chiral perovskites and strong electroacoustic coupling, the present invention is based on the stepped band structure of three-layer nanosheets and utilizes efficient interface spin-polarized carrier transmission to achieve strong circularly polarized luminescence characteristics at room temperature in achiral perovskite A, and the polarization degree at room temperature can reach 28.5%, which is of great significance to the application of circularly polarized light characteristics based on perovskite materials.
[0005] The present invention provides a method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite. Up to now, there is almost no report that can realize room temperature strong circularly polarized luminescence in non-chiral perovskite. Compared with the traditional realization of circularly polarized luminescence in chiral perovskite, the present invention realizes room temperature strong circularly polarized luminescence in non-chiral perovskite with advantages such as rich variety, high luminescence efficiency, weak electroacoustic coupling, and adjustable band gap, which can greatly broaden the application scope of perovskite-based circularly polarized luminescence.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: a method for realizing room temperature strong circularly polarized luminescence characteristics in achiral organic-inorganic hybrid perovskite, comprising the following steps:
[0007] S1: Obtain chiral perovskite nanosheets, achiral perovskite A nanosheets and achiral perovskite B nanosheets with a thickness of 5-20 nm respectively by mechanical exfoliation method;
[0008] S2: Using dry transfer technology to build a heterostructure of the above three, the stacking order is achiral perovskite A / achiral perovskite B / chiral perovskite / substrate;
[0009] S3: annealing the heterostructure at 60-90° C. for 3-10 minutes;
[0010] S4: Use the micro-area fluorescence spectrum test system to test the circularly polarized luminescence characteristics of the heterostructure;
[0011] In step S1, the chemical formula of the chiral perovskite is R-(C6H5C2H4NH3)2PbI4 or S-(C6H5C2H4NH3)2PbI4, and the chemical formula of the achiral perovskite A and the achiral perovskite B is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (1≤n≤4), (C4H9NH3)2(CH3NH3) n-1 Pb n I 3n+1 (1≤n≤4) or CH3NH3PbI3.
[0012] Preferably, in step S4, when testing the circularly polarized luminescence characteristics of the heterostructure, linearly polarized light is used to excite the heterostructure and its circularly polarized light emission is detected.
[0013] Preferably, the specific steps are as follows:
[0014] S1: Chiral perovskite R-(C6H5C2H4NH3)2PbI4 nanosheets and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) obtained by mechanical exfoliation n-1 Pb n I 3n+1 (n=4) nanosheets and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=2) nanosheets, whose thicknesses are 7 nm, 9 nm, and 11 nm, respectively;
[0015] S2: Use dry transfer technology to build a heterostructure of the above three, and the stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=4) / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I3n+1 (n=2) / R-(C6H5C2H4NH3)2PbI4 / silicon substrate;
[0016] S3: annealing the heterostructure at 70°C for 5 minutes;
[0017] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure area n-1 Pb n I 3n+1 The room temperature polarization degree of circularly polarized luminescence (n=4) can reach 28.5%.
[0018] Beneficial effects:
[0019] Based on the stepped band structure of the three-layer heterostructure, the efficient transmission of interface spin-polarized electrons is utilized to accumulate more spin-polarized electrons in the achiral perovskite A with a lower conduction band position, thereby making the achiral perovskite A have strong CPL characteristics (see Appendix Figure 2 ).
[0020] The present invention is based on the stepped band structure of three-layer nanosheets and utilizes efficient interface spin-polarized carrier transport to achieve strong circularly polarized luminescence characteristics at room temperature in achiral perovskite A. The room temperature polarization degree can reach 28.5%, which is of great significance for applications based on the circularly polarized light characteristics of perovskite materials.
[0021] The present invention provides a method for realizing room temperature strong circularly polarized luminescence characteristics in achiral organic-inorganic hybrid perovskite. Up to now, there is almost no report that can realize room temperature strong circularly polarized luminescence in achiral perovskite.
[0022] Compared with the traditional circularly polarized luminescence in chiral perovskites, the present invention realizes room temperature strong circularly polarized luminescence in achiral perovskites with the advantages of rich varieties, high luminescence efficiency, weak electroacoustic coupling, and adjustable band gap, which can greatly broaden the application scope of perovskite-based circularly polarized luminescence.
[0023] It can be seen from Examples 1-5 that the non-chiral organic-inorganic hybrid perovskite prepared in Example 1 achieves the best room temperature strong circularly polarized luminescence properties. The above three are constructed into a heterostructure through a microscopic transfer platform, and the stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=4) / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1(n=2) / R-(C6H5C2H4NH3)2PbI4 / silicon substrate, using the micro-region fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light, and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure region n-1 Pb n I 3n+1 The room temperature circularly polarized luminescence polarization degree of (n=4) can reach 28.5% (see Appendix Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the side composition of the heterostructure in the present invention.
[0025] Figure 2 Schematic diagram of the stepped energy band of the heterostructure in the present invention.
[0026] Figure 3 This is an optical photograph of the heterostructure prepared in Example 1.
[0027] Figure 4 The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterojunction in Example 1 n-1 Pb n I 3n+1 Circularly polarized luminescence spectrum of (n=4).
[0028] Figure 5 This is the circularly polarized luminescence spectrum of the achiral perovskite CH3NH3PbI3 in the heterojunction in Example 2. DETAILED DESCRIPTION
[0029] The present invention will be further described below in conjunction with the embodiments.
[0030] Embodiment 1:
[0031] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0032] S1: Chiral perovskite R-(C6H5C2H4NH3)2PbI4, achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n- 1Pb n I 3n+1 (n=4) and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1The (n=2) bulk single crystals were placed on low-viscosity tapes for mechanical peeling, folded in half several times, and then adhered to a polydimethylsiloxane substrate to obtain the corresponding nanosheets, whose thicknesses were 7nm, 9nm and 11nm, respectively; the above bulk single crystals were purchased from Shanghai Anwei Technology Co., Ltd.
[0033] S2: The above three are used to build a heterostructure through a microscopic transfer platform. The stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=4) / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=2) / R-(C6H5C2H4NH3)2PbI4 / silicon substrate (see attached Figure 3 ); The microscopic transfer platform was purchased from Nanjing Meta Optoelectronics Technology Co., Ltd.
[0034] S3: Anneal the heterostructure at 70°C for 5 minutes:
[0035] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure area n-1 Pb n I 3n+1 The room temperature circularly polarized luminescence polarization degree of (n=4) is 28.5% (see Appendix Figure 4 ).
[0036] Embodiment 2:
[0037] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0038] S1: chiral perovskite S-(C6H5C2H4NH3)2PbI4 nanosheets and non-chiral perovskite (C4H9NH3)2(CH3NH3) obtained by the mechanical exfoliation method mentioned in Example 1 n-1 Pb n I 3n+1 (n=3) nanosheets and achiral perovskite CH3NH3PbI3 nanosheets, whose thicknesses are 5nm, 15nm and 20nm, respectively;
[0039] S2: Use the micro-transfer platform to build a heterostructure of the above three, and the stacking order from top to bottom is CH3NH3PbI3 / (C4H9NH3)2(CH3NH3) n-1 Pbn I 3n+1 (n=3) / S-(C6H5C2H4NH3)2PbI4 / silicon substrate;
[0040] S3: Anneal the heterostructure at 60°C for 3 minutes:
[0041] S4: Using the micro-region fluorescence spectrum test system, the heterostructure is excited by linearly polarized light to detect its circularly polarized light emission. The room temperature circularly polarized luminescence polarization degree of the non-chiral perovskite CH3NH3PbI3 in the heterojunction region is 19.2% (see Appendix Figure 5 ).
[0042] Example 3
[0043] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0044] S1: Chiral perovskite R-(C6H5C2H4NH3)2PbI4, achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n- 1Pb n I 3n+1 (n=3) and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 The (n=1) bulk single crystals were placed on low-viscosity tapes for mechanical peeling, folded several times, and then adhered to a polydimethylsiloxane substrate to obtain the corresponding nanosheets, whose thicknesses were 3nm, 8nm and 10nm, respectively; the above bulk single crystals were purchased from Shanghai Anwei Technology Co., Ltd.
[0045] S2: The above three are used to build a heterostructure through a microscopic transfer platform. The stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=3) / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=1) / R-(C6H5C2H4NH3)2PbI4 / silicon substrate; the micro-transfer platform was purchased from Nanjing Meta Optoelectronics Technology Co., Ltd.
[0046] S3: Anneal the heterostructure at 65°C for 5 minutes:
[0047] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure area n-1 Pb n I 3n+1 The room temperature circularly polarized luminescence polarization degree of (n=3) is 19.5%.
[0048] Example 4
[0049] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0050] S1: Chiral perovskite S-(C6H5C2H4NH3)2PbI4, achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n- 1Pb n I 3n+1 (n=4) and non-chiral perovskite CH3NH3PbI3 bulk single crystals were placed on low-viscosity tape specially used for mechanical peeling, folded in half several times, and then glued to a polydimethylsiloxane substrate to obtain the corresponding nanosheets, whose thicknesses were 5nm, 7nm and 14nm, respectively; the above bulk single crystals were purchased from Shanghai Anwei Technology Co., Ltd.
[0051] S2: The above three are used to build a heterostructure through a microscopic transfer platform. The stacking order from top to bottom is CH3NH3PbI3 / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=4) / S-(C6H5C2H4NH3)2PbI4 / silicon substrate; the micro-transfer platform was purchased from Nanjing Meta Optoelectronics Technology Co., Ltd.
[0052] S3: Anneal the heterostructure at 65°C for 5 minutes:
[0053] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light to detect its circularly polarized light emission. The room temperature circularly polarized luminescence polarization degree of the non-chiral perovskite CH3NH3PbI3 in the heterostructure area is 17.1%.
[0054] Example 5
[0055] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0056] S1: Chiral perovskite R-(C6H5C2H4NH3)2PbI4, achiral perovskite (C4H9NH3)2(CH3NH3) n- 1Pb n I 3n+1 (n=1) and achiral perovskite CH3NH3PbI3 bulk single crystals were placed on low-viscosity tape specially used for mechanical peeling, folded in half several times, and then glued to a polydimethylsiloxane substrate to obtain the corresponding nanosheets, whose thicknesses were 7nm, 17nm and 15nm, respectively; the above bulk single crystals were purchased from Shanghai Anwei Technology Co., Ltd.
[0057] S2: The above three are used to build a heterostructure through a microscopic transfer platform. The stacking order from top to bottom is CH3NH3PbI3 / (C4H9NH3)2(CH3NH3) n-1 Pb n I 3n+1 (n=1) / R-(C6H5C2H4NH3)2PbI4 / silicon substrate; the micro-transfer platform was purchased from Nanjing Meta Optoelectronics Technology Co., Ltd.
[0058] S3: Anneal the heterostructure at 65°C for 10 minutes:
[0059] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light to detect its circularly polarized light emission. The room temperature circularly polarized luminescence polarization degree of the non-chiral perovskite CH3NH3PbI3 in the heterostructure area is 18.4%.
[0060] Comparative Example 1
[0061] A method for realizing room temperature strong circularly polarized luminescence characteristics in non-chiral organic-inorganic hybrid perovskite, the specific implementation steps are as follows:
[0062] S1: Chiral perovskite S-(C6H5C2H4NH3)2PbI4 and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n- 1Pb n I 3n+1 The (n=2) bulk single crystals were placed on low-viscosity tapes for mechanical peeling, folded several times, and then adhered to a polydimethylsiloxane substrate to obtain the corresponding nanosheets, whose thicknesses were 7.4 nm and 17 nm, respectively; the above bulk single crystals were purchased from Shanghai Anwei Technology Co., Ltd.
[0063] S2: The above two are built into a double-layer heterostructure through a microscopic transfer platform, and the stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1(n=2) / S-(C6H5C2H4NH3)2PbI4 / silicon substrate; micro-transfer platform was purchased from Nanjing Meta Optoelectronics Technology Co., Ltd.
[0064] S3: Anneal the heterostructure at 70°C for 5 minutes:
[0065] S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure area n-1 Pb n I 3n+1 The polarization degree of circularly polarized luminescence at room temperature (n=2) is only 5%.
[0066] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.
Claims
1. A method for achieving room temperature strong circularly polarized luminescence properties in non-chiral organic-inorganic hybrid perovskite, characterized in that: The following steps are involved: S1: Obtain chiral perovskite nanosheets, achiral perovskite A nanosheets and achiral perovskite B nanosheets with a thickness of 5-20 nm respectively by mechanical exfoliation method; S2: Using dry transfer technology to build a heterostructure of the above three, the stacking order is achiral perovskite A / achiral perovskite B / chiral perovskite / substrate; S3: annealing the heterostructure at 60-90 °C for 3-10 minutes; S4: Use the micro-area fluorescence spectrum test system to test the circularly polarized luminescence characteristics of the heterostructure; In step S1, the chemical formula of the chiral perovskite nanosheet is R-(C6H5C2H4NH3)2PbI4 or S-(C6H5C2H4NH3)2PbI4, and the chemical formula of the achiral perovskite A nanosheet and the achiral perovskite B nanosheet is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 ,1 ≤ n ≤4, (C4H9NH3)2(CH3NH3) n-1 Pb n I 3n+1 , 1 ≤ n ≤4 or CH3NH3PbI3, based on the stepped band structure of the three-layer nanosheets, and utilizing the interfacial spin-polarized carrier transport, room-temperature circularly polarized luminescence characteristics are realized in achiral perovskite A.
2. The method for realizing room temperature strong circularly polarized luminescence characteristics in achiral organic-inorganic hybrid perovskite according to claim 1, characterized in that: In step S4, when testing the circularly polarized luminescence characteristics of the heterostructure, the heterostructure is excited by linearly polarized light to detect the emission of circularly polarized light.
3. The method for realizing room temperature strong circularly polarized luminescence characteristics in achiral organic-inorganic hybrid perovskite according to claim 1, characterized in that: The specific steps are as follows: S1: Chiral perovskite R-(C6H5C2H4NH3)2PbI4 nanosheets and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) obtained by mechanical exfoliation n-1 Pb n I 3n+1 , n = 4 nanosheets and achiral perovskite (C6H5C2H4NH3)2(CH3NH3) n- 1Pb n I 3n+1 , n = 2 nanosheets, and their thicknesses are 7 nm, 9 nm, and 11 nm, respectively; S2: Use dry transfer technology to build a heterostructure of the above three, and the stacking order from top to bottom is (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 , n = 4 / (C6H5C2H4NH3)2(CH3NH3) n-1 Pb n I 3n+1 , n = 2 / R-(C6H5C2H4NH3)2PbI4 / silicon substrate; S3: annealing the heterostructure at 70 °C for 5 minutes; S4: Using the micro-area fluorescence spectroscopy test system, the heterostructure is excited by linearly polarized light and its circularly polarized light emission is detected. The non-chiral perovskite (C6H5C2H4NH3)2(CH3NH3) in the heterostructure area n-1 Pb n I 3n+1 The room temperature polarization degree of circularly polarized luminescence with n = 4 can reach 28.5%.
Citation Information
Patent Citations
Chiral perovskite luminescent material and preparation method and application thereof
CN114605994A
Circularly polarized light-emitting perovskite quantum dot and preparation method thereof
CN114621748A